Recent advances in Sn-based lead-free solder interconnects for microelectronics packaging: materials and technologies - Dele-Afolabi, T.T.; Ansari, M.N.M.; Azmah Hanim, M.A.; Oyekanmi, A.A.; Ojo-Kupoluyi, O.J.; Atiqah, A. (Elsevier Editora Ltda, 2023)
The electronic industry faces a number of issues as a result of the rapid miniaturization of electronic products and the expansion of application areas, with the reliability of electronic packaging materials playing a significant role. Moreover, the continuously harsh service conditions of electronic products like high current density and excessive Joule heat will lead to severe reliability concerns of electromigration and thermomigration, which evidently curtail the lifespan of solder joints. Therefore, to maintain the reliability of solder joints in recent microelectronic applications, several investigations have been conducted in the last decade to proffer solutions to the drawbacks affecting the full implementation of the Sn-based solders in advanced packaging technologies. This article reviews the recent developments on the reliability investigation of Sn-based solder joints and discusses the influence of interlayer materials, electroless nickel immersion silver (ENImAg) surface finish, geopolymer ceramics and rotary magnetic field (RMF) technology. The 3D network structure of porous interlayer metals and the beneficial features of ENImAg surface finish have demonstrated to be highly efficient in revamping existing lead-free solders by satisfying the needs of both high-temperature service operation and low-temperature soldering. While transient current bonding technology is efficient at preventing agglomeration and floating of nano-sized reinforcements in composite solders, RMF technology is effective in controlling the flow and solidification of liquid metal during the soldering process. Finally, emerging technologies for future research directions have been summarized to provide further theoretical basis required for the investigation of solder joint reliability of electronic devices in service.